Sphingolipids and mitochondrial function in budding yeast - Spincemaille, Pieter; Matmati, Nabil; Hannun, Yusuf A.; Cammue, Bruno P.A.; Thevissen, Karin (Biochimica et biophysica acta, 2014)
Sphingolipids (SLs) are not only key components of cellular membranes, but also play an important role as signaling molecules in orchestrating both cell growth and apoptosis. In Saccharomyces cerevisiae, three complex SLs are present and hydrolysis of either of these species is catalyzed by the inositol phosphosphingolipid phospholipase C (Isc1p). Strikingly, mutants deficient in Isc1p display several hallmarks of mitochondrial dysfunction such as the inability to grow on a non-fermentative carbon course, increased oxidative stress and aberrant mitochondrial morphology. In this review, we focus on the pivotal role of Isc1p in regulating mitochondrial function via SL metabolism, and on Sch9p as a central signal transducer. Sch9p is one of the main effectors of the target of rapamycin complex 1 (TORC1), which is regarded as a crucial signaling axis for the regulation of Isc1p-mediated events. Finally, we describe the retrograde response, a signaling event originating from mitochondria to the nucleus, which results in the induction of nuclear target genes. Intriguingly, the retrograde response also interacts with SL homeostasis. All of the above suggests a pivotal signaling role for SLs in maintaining correct mitochondrial function in budding yeast. Studies with budding yeast provide insight on SL signaling events that affect mitochondrial function. •Sphingolipids (SLs) are components of cellular membranes and signaling molecules.•Isc1p-mediated phytoceramide generation is crucial for mitochondrial function.•In response to SLs Sch9p transduces signals to regulate mitochondrial function.•The retrograde response affects SL homeostasis.•SLs are important signaling molecules in the regulation of mitochondrial function.